Material‐Independent 3D Patterning Via Two‐Photon Lithography and Discontinuous Wetting. Issue 5 (10th October 2022) - Dong, Zheqin; Monti, Joël; Cui, Haijun; Welle, Alexander; Singaraju, Surya A.; Blasco, Eva; Levkin, Pavel. A.
Abstract: The fabrication of complex 3D structures composed of micrometer‐sized features made of different functional materials is an immensely important and yet highly challenging task. Here, a method is developed to fabricate multimaterial 3D structures with micrometer precision by combining macroscopic 3D printing (digital light processing), with two‐photon lithography (2PL) and material‐independent discontinuous dewetting. Specifically, 3D inherently superhydrophobic objects are first printed by DLP, followed by creating hydrophilic micropatterns on their surface using 2PL. By exploiting the effect of discontinuous wetting, the selective deposition of solutions of functional materials into microscopic hydrophilic regions on the surface of 3D structures, with high resolution and great design flexibility is demonstrated. Importantly, the method is material‐independent and enables the micropatterning of a variety of functional materials dispersed in aqueous solutions including polydopamine, silica, or Ag nanoparticles. As an exemplary application, it is shown that conductive Ag electrodes can be created on the curved surface of 3D‐printed objects to construct structural electronics. The flexibility, high resolution, and material diversity in designing multimaterial 3D structures open exciting new functionalities and possibilities in a variety of applications including advanced electronics, soft robotics, and chemical or bioengineering. Abstract : A novel method for material‐independent micropatterning of 3D surfaces is developed by combining two‐photon lithography and discontinuous wetting. The selective deposition of different functional materials (including dyes, polydopamine, nanoparticles) is realized both on the upper surface and side areas of 3D objects, with very high spatial resolution and geometrical freedom.